A developmental state: How to allocate electricity efficiently in a developing country. (March 2020) - Fu, Tong; Jian, Ze
Abstract: Fossil fuel has been the main raw material in electricity generation though it is also the source of greenhouse gases and anthropogenic emissions from air pollution. To minimize the consumption of fossil fuel out of environmental concern, electricity needs to be allocated efficiently. Mainstream economics advocates arm's-length regulation in allocation of utility products, but regulatory systems in most developing countries are underdeveloped. To the best of our knowledge, this paper offers the first attempt to identify that the trajectory of a developmental state is an option to a developing country. With micro-evidence from China, we document that more reliable electricity is supplied to firms with high value added, with robustness to the potential endogeneity bias. Thus, we find that electricity-allocation efficiency in China is positive and causally meaningful. As we further show, three important conditions of a developmental state determine allocative efficiency: political stability promotes allocative efficiency; whereas both corruption and harmful tax policies reduce allocative efficiency. Ultimately, we show that electricity in a developing country can be allocated efficiently by a developmental state even though its utility regulations are not mature. Highlights: The allocative efficiency of electricity is important for sustainable development. The trajectory of a developmental state is an option to a developing country. Important conditions of a developmental state determine the allocative efficiency.